Cuidados paliativos: relação dialógica entre enfermeiros e crianças com câncer - França, Jael Rubia Figueiredo de Sá (2011)
INTRODUCTION: palliative care encompasses a holistic approach of care to the patient without therapeutic healing possibilities, and to his or her family providing them a better life quality. Its application is of great importance as regards taking care of child with cancer in end-stage. OBJECTIVES: this study aims to investigate the assistant nurses´ understanding about palliative care; identify the strategies used by the nurses for the promotion of palliative care devoted to the child with cancer in end-stage; evaluate how the nurses use communication while taking care of a child with cancer, in end-stage; analyze how the dialogic relationship between nurse and child with cancer, in end-stage, occurs. METHODOLOGY: it is a field research of qualitative nature. The investigation scenario was the Pediatric Unit of a public hospital in the town of João Pessoa PB. Ten assistant nurses took part in this research. Eight of these professionals are female and two of them are male. With regard to data collection, the interview technique was used from a number of questions which were pertinent to the proposed objectives. Data collection occurred between April and June 2010. DATA ANALYSIS: the empirical material was submitted to the categorical content analysis based on the Humanistic Theory of Nursing from the following phases: practicing the nurse in order to achieve knowledge; the nurse knows the other intuitively; the nurse knows the other scientifically; the nurse summarizes the known realities in a complementary way; succession of the multiple aspect to the paradoxical unit as the nurse s internal process. Data obtained by means of the discourses expressed by the investigation participants were classified in the following thematic categories: nurses´ perception about palliative care practice; nurse s relationship with child, with cancer without therapeutic healing possibilities, and his or her family; promotion to end-stage care; strategies used for humanizing the existential suffering of the child with cancer and his or her family based on palliative care; nurse s communicational and interpersonal relationship with the child with cancer in end-stage and his or her family. RESULTS: this research showed the importance of an approach centered on these children referring to an authentic I YOU relationship carried out by the nurses with the mentioned children and based on palliative care, promoting thus the development of a therapeutic process. The results also presented that the nurses use appropriate and useful strategies and that they care for the children s and their families needs as concerns the attention context cited in its entire dimension. FINAL COMMENTS: this leads to the conclusion that the researched nurses share genuine care with the cited children and their families, being thus sensitive from a holistic perspective and based on respect to their singularity. This research provides a new viewpoint with reference to the care, teaching and research field in nursing, with emphasis on the valorization of the dialogic relationship between nurses and children with cancer in end-stage, having as central concern palliative care. This study intends to prompt new investigations about the theme because researches, focusing on palliative care inter-relation with the Humanistic Theory with children experiencing cancer in end-stage, are still insignificant.